2020
DOI: 10.2174/1570159x18666191230114339
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and Melatonergic Influence on Neuronal Transcription Factors: Implications for the Development of Novel Therapies for Neurodegenerative Disorders

Abstract: : Melatonin is a multifunctional signalling molecule that is secreted by the mammalian pineal gland, and also found in a number of organisms including plants and bacteria. Research has continued to uncover an ever-increasing number of processes in which melatonin is known to play crucial roles in mammals. Amongst these functions is its contribution to cell multiplication, differentiation and survival in the brain. Experimental studies show that melatonin can achieve these functions by influencing transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 165 publications
1
5
0
Order By: Relevance
“…This could suggest that patients treated with thrombolysis have impaired urinary excretion of the metabolite and low antioxidant protection. Similarly, a reduced level of serum melatonin and its metabolites in the urine of patients with stroke has been confirmed by other researchers [ 23 , 24 , 25 , 26 , 27 ]. In our study, an increase in the concentration of the melatonin metabolite was observed within the first 24 h compared to its level before <4.5 h in patients treated with thrombolytic therapy.…”
Section: Discussionsupporting
confidence: 72%
“…This could suggest that patients treated with thrombolysis have impaired urinary excretion of the metabolite and low antioxidant protection. Similarly, a reduced level of serum melatonin and its metabolites in the urine of patients with stroke has been confirmed by other researchers [ 23 , 24 , 25 , 26 , 27 ]. In our study, an increase in the concentration of the melatonin metabolite was observed within the first 24 h compared to its level before <4.5 h in patients treated with thrombolytic therapy.…”
Section: Discussionsupporting
confidence: 72%
“…Melatonin is known to have a variety of biological functions, including circadian rhythm regulation, anti-inflammatory, free radical scavenging, edema reduction, suppression of the hypothalamic-pituitary endocrine axis, suppression of cancer, stimulation of mitochondrial biogenesis, immunomodulation, blood pressure regulation and the epigenetic regulation, and has therapeutic effects on a variety of secondary injuries after SCI ( Giannoulia-Karantana et al, 2006 ; de Faria Poloni et al, 2011 ; Mazzoccoli et al, 2011 ; Xu L.X. et al, 2017 ; Chang et al, 2018 ; Onaolapo et al, 2020 ; Cho et al, 2021 ; Vasey et al, 2021 ). Melatonin can also regulate the intestinal biological clock and the types of intestinal microbiota, improve the metabolic disorder caused by intestinal microbiota imbalance after SCI, and indirectly play a role in the recovery of function and the treatment of complications ( Paulose et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The chief function of melatonin is to transmit information on the daily light and darkness cycle (Claustrat et al 2005 ) and it plays a key role in the regulation of the sleep-awakeness cycle, puberty development, seasonal adaptation and memory formation (Giannoulia-Karantana et al 2007 ; Skarlis and Anagnostouli 2020 ). Furthermore, melatonin is known to be a multifunctional molecule (Onaolapo et al 2019 ), and has been seen to have an anti-oxidant, anti-inflammatory (Escribano et al 2014 ) and anti-apoptotic capacity, as well as acting in immune responses and mitochondrial homeostasis (Carrascal et al 2018 ) contributing to the multiple cell differentiation and survival in the brain (Onaolapo et al 2019 ).…”
Section: Melatonin: Synthesis Secretion Receptors and Functionmentioning
confidence: 99%